Mating status drives fitness trade-offs in exercised female Drosophila - Anne E. Backlund; Meghan Green; Emie K. Vandiver; Laura K. Reed (PLoS ONE, 2025)
Regular physical exercise has been shown to improve physical and psychological well-being through a variety of mechanisms; however, the degree to which different individuals respond to exercise varies depending on sex and genetic factors. Drosophila has been used as a model organism to further understand the molecular mechanisms that underlie exercise adaptation. Essential for flies’ ability to adapt to exercise, octopamine is a hormone and neurotransmitter found in invertebrates that is analogous to norepinephrine. Interestingly, octopamine is also crucial for female post-mating responses, and no studies to date have explored the interaction between exercise response and reproductive state in females. Here, we investigated the sexual dimorphism in exercise response by exercising male and female flies of multiple Drosophila Genetics Reference Panel (DGRP) lines and measuring fitness traits such as climbing ability and starvation resistance. Further, we were interested in how mating status might affect females’ ability to adapt to exercise, and whether the stress of exercise would affect fertility. Our findings show that while male flies are naturally faster climbers than female flies, females tend to be better suited to resist starvation. Additionally, we found that mating status has a significant impact on female flies’ climbing performance and lifespan, and exercise can have negative effects on lifespan and fertility. Surprisingly, we found that exercise has little effect on stored triglycerides, protein levels, or gene expression. DGRP genetic line was also a significant factor that influenced most phenotypes we measured, underscoring the importance of studying multiple genotypes in conjunction with other experimental variables. Results from our study suggest that female flies may experience evolutionary trade-offs between physical activity, survival, and fertility, and whether the female has mated or not dictates how they respond to physiological stressors such as exercise.